Case Method and Scaffolding Technique Assisted by Supporting Technology: An Attempt to Train Students’ Academic Writing - Stephani Diah Pamelasari; Risa Dwita Hardianti; Fahrur Rozi (Yayasan Keluarga Guru Mandiri, 2023)
Students still have problems achieving adequate writing skills in academic writing. Hence, the case method, scaffolding, and supporting technology are applied to help students improve their academic writing skills in the English for Specific Purpose (ESP) course. Therefore, this study aims to analyze the effectiveness of the case method and scaffolding technique assisted by supporting technology to train students' academic writing in ESP courses. The research was experimental research with a post-test-only non-equivalent control group design. The samples were 50 students of the Environmental Science Study Program. The instruments were the performance test of writing an essay and a questionnaire to determine students' responses to the learning process. The result shows Sig. (2 tailed) 0,05, indicating there is a difference between the academic writing of the experimental group and the control group. The mean score and writing aspect assessment of the experimental group are also higher than the control group. Therefore, it can be concluded that the case method and scaffolding technique assisted by supporting technology is effective in training students' academic writing, and it also reveals the case method's role in improving students' skills.